Monitoring and Control the Supply of Fuel in Baghdad using RFID - Hasan, Mohannad M.; Al-Naima, Fawzi M. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
Nowadays, there are no accurate records of the various quantities of fuel being dispensed at the Iraqi fuel stations. All such reports are usually paper-based and are missing the required precision to control this valuable commodity, which could lead to misuse or illegal sale of fuel. This paper presents a control system based on RFID technology to monitor the supply and dispensing of vehicle fuel in Baghdad. The system consists of RFID readers attached to fuel dispensers and pumps, and RFID tags assigned to the vehicles and the trucks used for delivering fuel to the fuel stations. A hardware part is connected to conventional fuel dispensers and machines, located at both the stations and the fuel refineries or depots, which makes them work under the control of the RFID system, without the need to rebuild new dispensers. The designed system database is a centralized one located on a cloud server, in order to allow fuel stations to communicate with it and do the required transactions. Throughout this system, different reports can be generated, which can give important online statistics about the movement of fuel supplies over the city.